Du fait divers médiatique à la critique sociale, représentation du 11 septembre dans Une lueur d'espoir de Marc-Édouard Nabe - Mahy, Fanny (2011)
On September 11th, Marc-Édouard Nabe wrote his reactions to the attacks, Une lueur despoir. It was immediately written off by the reading public as an apology for terrorism, and it did not fare better with academics, engendering little ink from the critics who considered it a provocation and a scandal. The text requires, however, a more nuanced approach. Nabe is clearly saddened by the human loss, and his primary aim seems to be focused not on the attacks, but rather on their coverage. Coverage he views as portraying the events in a spectacular fashion, aimed at preventing any reflection. In this paper, I argue that without ever using the word fait divers, Nabe is referring to, and speaking out against this category of information. He moves from seeing the event, le fait, as an accumulation of personal tragedies towards seeing it as collective event. The attacks then take on a mainly societal, but also mythical, historic, and metaphysical dimension. The social aspect is so manifest that September 11 is then no more than a pattern that functions as a pretext to develop a critique of Western Americanized society.